1998
DOI: 10.4141/a97-087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alfalfa and fenugreek (Trigonella foenum-graecum) silages supplemented with barley grain on performance of growing steers

Abstract: .Comparison of alfalfa and fenugreek (Trigonella foenum-graecum) silages supplemented with barley grain on performance of growing steers. Can. J. Anim. Sci. 78: 343-349. To compare nutritive value of alfalfa and fenugreek silages for weaned backgrounding feedlot steers, isonitrogenous diets of alfalfa or fenugreek silage, supplemented with three levels of steam-rolled barley (0, 15 and 30% DM) were fed ad libitum to 60 steers (initial weight of 237 ± 18 kg). The study was conducted in individual pens for 105 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
3
17
1
1
Order By: Relevance
“…In contrast to our results, no difference in DMI was reported by Mir et al (1998) for steers fed alfalfa and fenugreek silage (harvested at 17 weeks of age) supplemented with barley grain. It is possible that fenugreek refusal only occurs at high DMIs as seen in dairy cows, or that short-cut silage is more palatable than long-stemmed haylage.…”
Section: Dmi and Productioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our results, no difference in DMI was reported by Mir et al (1998) for steers fed alfalfa and fenugreek silage (harvested at 17 weeks of age) supplemented with barley grain. It is possible that fenugreek refusal only occurs at high DMIs as seen in dairy cows, or that short-cut silage is more palatable than long-stemmed haylage.…”
Section: Dmi and Productioncontrasting
confidence: 99%
“…The similarity of individual major VFA concentrations and rumen pH among treatments is in agreement with Mir et al (1998) who reported no difference in rumen pH and acetic and BCFA concentrations for growing steers fed fenugreek-and alfalfa-based diets supplemented with different levels of barley grain. The higher concentration of total VFA for cows fed the ALF diet could be due to their higher energy intake.…”
Section: Plasma Metabolites Studies In Rats (supporting
confidence: 90%
See 2 more Smart Citations
“…The data were obtained from a study by Mir et al (1998) in which 60 crossbred steers (initial weight 237 ± 18 kg) were individually fed one of six diets with 10 steers per diet for 105 d. Feed intakes were individually recorded daily while steer weights were recorded at 21-d intervals. The six diets were: 100% alfalfa (Medicago sativa L.) silage, 85% alfalfa silage + 15% barley (Hordeum vulgare L.) grain, 70% alfalfa silage + 30% barley grain, 100% fenugreek (Trigonella foenum graecum L.) silage, 85% fenugreek silage + 15% barley grain, and 70% fenugreek silage + 30% barley grain.…”
mentioning
confidence: 99%